Business Anthropology: A Socio-Cultural Approach to Global Market Penetration - Fernando Eko Mardiansyah; Muhammad Rendi Septriawan (Pustaka Bangsa Indonesia, 2026)
Global market expansion is frequently met with failure despite companies being supported by strong financial capital. These failures are generally rooted in an inability to understand the local cultural landscape. This article aims to explain why socio-cultural understanding—through the lens of business anthropology—is more crucial than financial capital for effective international market penetration. Using literature review and case study analysis, this journal examines how business anthropology helps companies navigate consumer behavior, social norms, and cultural symbols. Findings indicate that deep cultural adaptation (localization) generates consumer trust, brand loyalty, and long-term business sustainability. In conclusion, culture is a strategic asset, not merely a barrier, which requires an ethnographic approach to penetrate global markets.